2023
DOI: 10.3390/healthcare11071006
|View full text |Cite
|
Sign up to set email alerts
|

Utilizing Extracorporeal Shockwave Therapy for in-Season Athletes

Abstract: An athlete’s health and availability to train and compete at an optimal performance level is a growing focus for professional sports organizations [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Growing research has suggested that extracorporeal shockwave therapy (ESWT) may be effective for the management of sports-related injuries. 6 ESWT is a non-invasive intervention that creates sound or pressure waves that propagate through tissues to stimulate interstitial and extracellular responses. 7 Such biological responses include increased collagen synthesis, 8 cellular proliferation and wound healing, 9 10 and neovascularisation.…”
Section: Introductionmentioning
confidence: 99%
“…Growing research has suggested that extracorporeal shockwave therapy (ESWT) may be effective for the management of sports-related injuries. 6 ESWT is a non-invasive intervention that creates sound or pressure waves that propagate through tissues to stimulate interstitial and extracellular responses. 7 Such biological responses include increased collagen synthesis, 8 cellular proliferation and wound healing, 9 10 and neovascularisation.…”
Section: Introductionmentioning
confidence: 99%
“…According to some studies, shock wave treatment may help decrease DOMS symptoms by increasing blood flow, tissue healing, and decreasing pain sensitivity. It is thought to hasten healing by boosting collagen formation and the release of growth factors [ 10 , 11 ]. However, the data is inconclusive, and further investigation is required to determine the efficacy of a single administration of focused shock wave treatment for DOMS.…”
Section: Introductionmentioning
confidence: 99%